Visualization of Two-Phase Flow Regime in Vertical Pipe Airlift pump - Fajarningrum, Nurmala Dyah; Hadi Sufyan, M. Fendy Kussuma; Fahadha, Rizqa Ula; Deendarlianto, Deendarlianto; Kurniawan, Dedy (Mechanical Engineering Department - Semarang State Polytechnic, 2024)
An airlift pump can be used to move from one location to another. The pump lifts liquid or solid particles from air bubbles through a vertical pipe. In this experiment, the airlift pump system was modified using a microbubble generator installed on the injector to produce air bubbles. Two injectors were installed with a swirl model. This study aims to visualise the flow pattern that forms in a vertical pipe when air bubbles lift water toward the endpoint. The flow pattern was observed by varying airspeed and water column h in the vertical pipe. The method in this study was carried out using a two-phase flow (air-water). An acrylic pipe with an inner diameter of 50 mm and a height of 327 cm was used in this study. The immersion ratios were set to 0.44, 0.50, 0.56, 0.62, and 0.68. Air was injected into the system through a compressor injector, and air release was controlled by an airflow meter. m ³/h, 1.5 m ³/h, 2 m ³/hour, 2.5 m ³/h, and 3 m ³/h. The flow pattern in the thriller pipe is captured using a video camera. The research results show that bubble, slug, churn, and annular flow patterns are formed owing to variations in the airflow injected into the system. The slug flow changed to an annular flow as the slug flow speed increased. The slug and churn flows lifted the water, and the annular flow reversed the buoyancy force of the slug and churn flows. This study concludes that the ratio of the water column height in the vertical pipe affects the driving force for lifting water to the separator. The greater the immersion ratio, the better is the pump performance. In addition, the influence of the injected airflow forms a flow pattern that can move water from the bottom to a certain height.